Attributive datamodel of national hydrogeolocical database to define groundwater bodies of Slovenia - Katarina Hribernik; Joerg Prestor (Geologija, 2004)
Hydrogeological investigations of groundwater are based on large amount of qualitative and quantitative data (hydrological, hydrogelological, geological, pedological, geomorfological, meteorological…), information about topography, land use, antropogenic elements and ecosystems, which demands a complex approach to modeling and organizing information into some logical structure of all purpose data model, useful on local, regional and national level. For that purpose at Geological survey of Slovenia we established a Database of hydrogeolocial data to define groundwater bodies of Slovenia in which all significant data of groundwater bodies, aquifers and hydrogeological objects are available. Digital storage of attributive data enables uniformity of standards for collecting, analyzing and management of data, their spatial presentation and distribution, connection with other information systems and important decision – making future analysis.